1990
DOI: 10.1210/endo-127-2-965
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor is Expressed in Rat Corpus Luteum

Abstract: In the course of the development of the ovarian follicle and differentiation of granulosa cells into corpus luteum (CL), extensive changes in the microvasculature of these structures take place. This suggests the local release of angiogenic factors. In the present work we examined whether a newly described secreted vascular endothelial growth factor (VEGF) is expressed in normal rat ovary by in situ hybridization. Our results demonstrate the expression of VEGF in the CL but not in mural granulosa cells, sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
119
0
3

Year Published

1991
1991
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 271 publications
(131 citation statements)
references
References 18 publications
9
119
0
3
Order By: Relevance
“…Our failure to demonstrate VPF transcripts in RNA prepared from randomly collected guinea pig ovaries very likely reflects the absence of sufficient numbers of corpora lutea in those ovaries for detection by Northern analysis. We have, however, demonstrated the presence of VPF protein in guinea pig corpus luteum by immunohistochemistry (Sioussat, unpublished data), providing support for and supplementing the findings of Phillips et al (1990).…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Our failure to demonstrate VPF transcripts in RNA prepared from randomly collected guinea pig ovaries very likely reflects the absence of sufficient numbers of corpora lutea in those ovaries for detection by Northern analysis. We have, however, demonstrated the presence of VPF protein in guinea pig corpus luteum by immunohistochemistry (Sioussat, unpublished data), providing support for and supplementing the findings of Phillips et al (1990).…”
Section: Discussionsupporting
confidence: 60%
“…Several other tissues were negative, but Northern analysis may be insufficiently sensitive to detect transcripts produced by only a small Molecular Biology of the Cell fraction of cells in a heterologous mixture even if those few cells produce significant levels of transcript. Earlier in situ hybridization experiments (Phillips et al, 1990) described VPF transcription in the corpus luteum but not elsewhere in the ovary, suggesting hormonally regulated cell-specific control of VPF expression. Our failure to demonstrate VPF transcripts in RNA prepared from randomly collected guinea pig ovaries very likely reflects the absence of sufficient numbers of corpora lutea in those ovaries for detection by Northern analysis.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Several lines of evidence suggest that vascular endothelial growth factor (VEGF) is a major regulator of physiological blood vessel growth, namely (1) it is a secreted endothelial cell specific mitogen (Ferrara and Henzel, 1989;Gospodarowicz et al, 1989;Plouet et al, 1989), (2) it induces angiogenesis in in vivo test systems (Connolly et al, 1989;Gospodarowicz et al, 1989), and (3) its expression correlates with phases of angiogenesis during embryogenesis and in the female reproductive cycle (Phillips et al, 1990;Breier et al, 1992;Shweiki et al, 1993). The observation that VEGF expression is upregulated in certain tumors, e.g., in glioblastoma (Plate et al, 1992;Shweiki et al, 1992;Phillips et al, 19931, indicated that VEGF may also regulate angiogenesis in tumors.…”
Section: Introductionmentioning
confidence: 99%